Multicellularity : from brief encounters to lifelong unions - Olson, Bradley J. (My University, 2014)
Could the transient aggregation of unicellular organisms have paved the way for the evolution of the multicellular animals?
Keywords: Multicellular organisms; Evolution; Clonal development; Aggregative development; Multicellularity